SlPHL1, a MYB‐CC transcription factor identified from tomato, positively regulates the phosphate starvation response. Issue 3 (24th July 2021) - Zhang, Yongqiang; Wang, Yi; Wang, Enhui; Wu, Xueqian; Zheng, Qinghua; Han, Yizhen; Lin, Weiwei; Liu, Zhongjuan; Lin, Wenxiong
Abstract: Inorganic phosphate (Pi) deficiency is a major limiting factor for plant growth and development. Previous reports have demonstrated that PHOSPHATE STARVATION RESPONSE 1 (PHR1) and OsPHR2 play central roles in Pi‐starvation signaling in Arabidopsis and rice, respectively. However, the Pi‐starvation signaling network in tomato ( Solanum lycopersicum ) is still not fully understood. In this work, SlPHL1, a homolog of AtPHR1 and OsPHR2, was identified from tomato. It was found that SlPHL1 contains the MYB and coiled‐coil (CC) domains, localizes in the nucleus, and has transcriptional activity, indicating that it is a typical MYB‐CC transcription factor (TF). Overexpression of SlPHL1 enhanced Pi‐starvation responses both in Arabidopsis Col‐0 and in tomato Micro‐Tom, including elevated root hair growth, promoted APase activity, favored Pi uptake, and increased transcription of Pi starvation‐inducing (PSI) genes. Besides, overexpressing SlPHL1 was able to compensate for the Pi‐starvation response weakened by the AtPHR1 mutation. Notably, electrophoretic mobility shift assay (EMSA) showed that SlPHL1 could bind to the PHR1‐binding sequence (P1BS, GNATATNC)‐containing DNA fragments. Furthermore, SlPHL1 specifically interacted with the promoters of the tomato PSI genes SlPht1 ; 2 and SlPht1 ; 8 through the P1BS cis ‐elements. Taken these results together, SlPHL1 is a newly identified MYB‐CC TF from tomato, which participates in Pi‐starvation signaling by directly upregulating the PSI genes. These findings might contribute to the understanding of the Pi‐starvation signaling in tomato.